The Investigation Process of Children Suspects in Narcotics Crime in National Anti Narcotics Agency (BNN) - Ageng Fajar Wicaksono; Siti Rodhiyah Dwi Istinah; Andi Aina Ilmih (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to find out and analyze the process of investigating child suspects in narcotics crimes in National Anti Narcotics Agency (BNN) and to find out and analyze the obstacles in the process of investigating child suspects in narcotics crimes in National Anti Narcotics Agency (BNN) and its solutions. The approach method used in this research is a sociological juridical approach. The sociological juridical approach is identifying and conceptualizing law as a real and functional social institution in a real life system. The sources and types of data in this study are secondary data. The method of data collection was obtained from a literature study. The data were analyzed descriptively analytically. The results of this study are the process of investigating child suspects in narcotics crimes at the National Anti Narcotics Agency (BNN) of Central Java Province are: Investigations into narcotics crimes include investigations, arrests, detentions, searches, confiscations. Investigations conducted by the Central Java Provincial BNN are in accordance with the Criminal Procedure Code and Act No. 35 of 2009 concerning Narcotics. Obstacles in the Investigation of Child Suspects in Narcotics Crimes at the National Anti Narcotics Agency (BNN) and the Solutions is time consuming compared to investigations in adult cases, investigators hope that the parties who participate in assisting the investigation process are expected to cooperate cooperatively, the lack of public awareness to report so that the police are expected to provide counseling to the public about narcotics crimes, the lack of the role of the family environment, as a parents should play an active role in taking care of their children by following the development of information or counseling if any, whether organized by the National Anti Narcotics Agency, investigators, doctors. Because parents play an important role in the socialization process of children. Therefore, parents must devote attention to educating their children so that these children get the right pattern of social life.